2023
DOI: 10.1039/d2ra06661k
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of magnetic nanoparticles by bacteriophages and ionic liquids precursors

Abstract: Magnetic nanoparticles can be modified with bacteriophages and quaternary ammonium salt (QAS), and can reveal different antibacterial properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 68 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Moreover, experimental studies also reveal the presence of similar angular structures 20 . It has been shown experimentally that viruses can both bind to mineral phases and influence mineral formation 16 , 20 , 21 . In addition, viruses present during calcium carbonate precipitation can affect both the particle size distribution of calcium carbonate and the formation of a metastable phase such as vaterite 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, experimental studies also reveal the presence of similar angular structures 20 . It has been shown experimentally that viruses can both bind to mineral phases and influence mineral formation 16 , 20 , 21 . In addition, viruses present during calcium carbonate precipitation can affect both the particle size distribution of calcium carbonate and the formation of a metastable phase such as vaterite 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Działak et al 19 . biosynthesized iron oxide magnetic nanoparticles using P1 and ɸ6 phages isolated from E. coli (P1), Pseudomonas syringae (ɸ6).…”
Section: Phage Used For the Biosynthesis Of Metal Nanoparticlesmentioning
confidence: 99%
“…This phage infects Pseudomonas syringae and is one of the prominent features of the lipid membrane around its capsid. 41 Działak et al 19 biosynthesized iron oxide magnetic nanoparticles using P1 and ɸ6 phages isolated from E. coli (P1), Pseudomonas syringae (ɸ6). In this study, 100 mL of iron chloride was mixed with 1 mL of phage suspension at a concentration of 1 × 10 10 PFU, then it was stirred at a temperature of 40 C with 600 rpm to cause a colour change, and finally, magnetic nanoparticles were separated using a magnet.…”
Section: P1 and ɸ6 Phagesmentioning
confidence: 99%
“…It has already been shown that bacteriophages potentially can affect the precipitation of various minerals (Działak et al., 2022; Działak & Borkowski et al., 2023; Działak & Syczewski et al., 2023; Słowakiewicz et al., 2021). It was suggested that bacteriophages can induce the formation of vaterite and change the agglomeration of mineral particles of carbonates (Słowakiewicz et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of data in this subject. Previous works have shown the possible influence of bacteriophages on the formation of framboid‐like structures and on magnetic properties (Działak, Syczewski, et al., 2023; Działak et al, 2022). However, more precise studies are still absent.…”
Section: Introductionmentioning
confidence: 99%